Skin senescence—from basic research to clinical practice - Natalia Dorf; Mateusz Maciejczyk (Frontiers in Medicine)
The most recognizable implications of tissue aging manifest themselves on the skin. Skin laxity, roughness, pigmentation disorders, age spots, wrinkles, telangiectasia or hair graying are symptoms of physiological aging. Development of the senescent phenotype depends on the interaction between aging cells and remodeling of the skin’s extracellular matrix (ECM) that contains collagen and elastic fiber. Aging changes occur due to the combination of both endogenous (gene mutation, cellular metabolism or hormonal agents) and exogenous factors (ultraviolet light, environmental pollutants, and unsuitable diet). However, overproduction of mitochondrial reactive oxygen species (ROS) is a key factor driving cellular senescence. Aging theories have disclosed a range of diverse molecular mechanisms that are associated with cellular senescence of the body. Theories best supported by evidence include protein glycation, oxidative stress, telomere shortening, cell cycle arrest, and a limited number of cell divisions. Accumulation of the ECM damage is suggested to be a key factor in skin aging. Every cell indicates a functional and morphological change that may be used as a biomarker of senescence. Senescence-associated β-galactosidase (SA-β-gal), cell cycle inhibitors (p16INK4a, p21CIP1, p27, p53), DNA segments with chromatin alterations reinforcing senescence (DNA-SCARS), senescence-associated heterochromatin foci (SAHF), shortening of telomeres or downregulation of lamina B1 constitute just an example of aging biomarkers known so far. Aging may also be assessed non-invasively through measuring the skin fluorescence of advanced glycation end-products (AGEs). This review summarizes the recent knowledge on the pathogenesis and clinical conditions of skin aging as well as biomarkers of skin senescence.